Do Lulu Movements in Italy Fight Mafia and Corruption? Framing processes and 'anti-system' struggles in the No Tav, No Bridge and No Muos case studies - Gianni Piazza (Coordinamento SIBA, 2018)
In this article, we focus on the way in which the LULU (Locally Unwanted Land Use) movements against great infrastructures have framed the issues of corruption and organized crime in Italy, with particular reference to the mafia system, and the struggle against them. Even though they may seem minor issues, they are present in many territorial struggles, from North to South: indeed, we have chosen to analyse – using documents and semi-structured interviews with key informants – as empirical cases the No Tav, No Bridge and No Muos movements. Considering the frame analysis of the activists we have found the same mechanisms of frame bridging, which connect corruption and mafia with other issues in the movements, and frame extension from the particular cases to the general issues. Moreover, the corrupt and mafia systems outlined by the Lulu activists merge into a unique "corrupt-mafia system" that produces unwanted public works. Indeed, we have defined the Lulu movements as territorial movements carrying on 'anti-system' struggles, because, while contrasting specific large-scale infrastructures and military bases, they struggle against the system that have created them and to which they belong.